Skin Stretching Techniques: A Review of Clinical Application in Wound Repair - Tian Yang, BS; Zhixiang Tan, MS; Xuejie Chen, PhD; Fang Wang, BS; Rui Tao, BS; Yilan Tong, MS; Xiaoli Wang, PhD; Huajun Fan, MS; Mosheng Yu, MS; Zhanyong Zhu, PhD (Plastic and Reconstructive Surgery, Global Open)
Background:. The repair of skin defect wounds is a long-term goal of clinical pursuit. Currently, free or pedicled skin flap transplantation is commonly used to repair skin defects. However, these methods may lead to complications such as flap necrosis, thrombosis, scarring, diminished sensation, and pigmentation in both the donor and recipient areas. Since its introduction in 1976, skin stretching techniques were widely used for minor skin and soft-tissue defects in the surgical field. Methods:. A narrative review was conducted to identify relevant articles about the skin stretching techniques for promoting wound healing. We searched the Web of Science and PubMed databases for all articles containing different combinations of “skin stretch techniques” and “wound repair,” “skin defects,” and “tissue expansion.” Results:. Through the screening of 500 articles, 84 representative and persuasive articles were selected in this review. These studies collectively demonstrate the technique’s effectiveness in reducing wound size, facilitating primary closure, and improving cosmetic outcomes. Reported complications were generally minor, including transient erythema and mild discomfort, with rare instances of skin necrosis. Conclusions:. Skin stretch techniques emerge as a promising approach for managing large-area wounds, offering the advantage of achieving primary healing without compromising surrounding healthy tissue. However, to optimize its clinical application, further research is warranted, particularly in addressing challenges related to precise stretching and infection management.